If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (100 * 0.1) + 100 = X Multiply 100 * 0.1 (10) + 100 = X 10 + 100 = X Combine like terms: 10 + 100 = 110 110 = X Solving 110 = X Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-1X' to each side of the equation. 110 + -1X = X + -1X Combine like terms: X + -1X = 0 110 + -1X = 0 Add '-110' to each side of the equation. 110 + -110 + -1X = 0 + -110 Combine like terms: 110 + -110 = 0 0 + -1X = 0 + -110 -1X = 0 + -110 Combine like terms: 0 + -110 = -110 -1X = -110 Divide each side by '-1'. X = 110 Simplifying X = 110
| X*0.1=100 | | 6x+11=2x-1 | | (-3)(3+2x)+4x^2+1(1-x)=-11 | | 18x-x^2=71 | | 3x-15y=0 | | 2a+11=15 | | 36*(25+48)-16*22= | | 2x+36=6x+3 | | 7+5x=42 | | H=-4.9t^2+80t | | 1+3x=16-2x | | 5a^2+22a+21=0 | | 2x+8=3x+6+8 | | 2y^2+19y=-24 | | x^3-15x^2+800=0 | | 6-8x=47-15x | | 4v-5=v+4 | | (x)(x+1)=14(2x+1)+44 | | x+786(y+z)=2526 | | 129-4x=4x+9 | | -6-4x=15-9x | | x+3x-3= | | x+2y=128 | | 2x-3x+1+8x=2x+5+4x-3 | | (x-5)(x).5=42 | | 6-8x=3-9x | | 4x+18=14x-62 | | (3x+5)(8x-2)=(3x)(8x)+(3x)(-2)+(5)(8x)+(5)(-2) | | 9x+28=4x+103 | | 49-3x=8x+19 | | 2x+3y-5z=1 | | 6x-5=8+5x |